Advanced grazing-incidence techniques for modern soft-matter materials analysis - Hexemer, Alexander; Müller-Buschbaum, Peter (IUCrJ, 2015)
The complex nano-morphology of modern soft-matter materials is successfully probed with advanced grazing-incidence techniques. Based on grazing-incidence small- and wide-angle X-ray and neutron scattering (GISAXS, GIWAXS, GISANS and GIWANS), new possibilities arise which are discussed with selected examples. Due to instrumental progress, highly interesting possibilities for local structure analysis in this material class arise from the use of micro- and nanometer-sized X-ray beams in micro- or nanofocused GISAXS and GIWAXS experiments. The feasibility of very short data acquisition times down to milliseconds creates exciting possibilities for in situ and in operando GISAXS and GIWAXS studies. Tuning the energy of GISAXS and GIWAXS in the soft X-ray regime and in time-of flight GISANS allows the tailoring of contrast conditions and thereby the probing of more complex morphologies. In addition, recent progress in software packages, useful for data analysis for advanced grazing-incidence techniques, is discussed.